2003
DOI: 10.1519/1533-4287(2003)017<0556:natswb>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Adaptation to Short-Term (4 Weeks) Ballistic Training in Trained High School Athletes

Abstract: The effects of a 4-week ballistic training program on neurological adaptation in trained high school athletes was assessed. Thirty-eight senior high school athletes (12 young women and 26 young men) were randomly assigned to either an experimental group (EXP, n = 20) or a control group (CON, n = 18). The only alteration in training was that EXP engaged in a new type of ballistic training over the 4-week experimental period. Measurements included total body weight (TBW), sum of skinfolds (SS), thigh circumferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This specificity is also supported by the agreement found between magnitude and orientation of the mechanical outputs analyzed and the sport discipline and level at which it is practiced. When analyzing the existing literature in light of the present results, it is interesting to note that precisely in those studies where the relationship between “horizontal” and “vertical” performances was strong, either low-level athletes were tested ( Coutts, Murphy & Dascombe, 2004 ; Cormie, McGuigan & Newton, 2010 ) or the tested populations were not sub-categorized by gender, level of practice, or sport discipline, which may have influenced data interpretation ( Hammett & Hey, 2003 ; Deane et al, 2005 ). In this regard, our results generally revealed larger correlations between the variables of the FVP profile as well as for the performance variables (SJ height and sprint time to 20 m) when the data were not sub-categorized.…”
Section: Discussionmentioning
confidence: 92%
“…This specificity is also supported by the agreement found between magnitude and orientation of the mechanical outputs analyzed and the sport discipline and level at which it is practiced. When analyzing the existing literature in light of the present results, it is interesting to note that precisely in those studies where the relationship between “horizontal” and “vertical” performances was strong, either low-level athletes were tested ( Coutts, Murphy & Dascombe, 2004 ; Cormie, McGuigan & Newton, 2010 ) or the tested populations were not sub-categorized by gender, level of practice, or sport discipline, which may have influenced data interpretation ( Hammett & Hey, 2003 ; Deane et al, 2005 ). In this regard, our results generally revealed larger correlations between the variables of the FVP profile as well as for the performance variables (SJ height and sprint time to 20 m) when the data were not sub-categorized.…”
Section: Discussionmentioning
confidence: 92%
“…Expanding on the total intervention period, Fischetti [33] et al concluded that in order to improve jumping and speed performance in adolescent athletes, the minimum duration of plyometric training must be at least 6 weeks [17,70]. In terms of speed improvement, the trained population was more responsive to various training stimulus than the untrained [71].…”
Section: Sprint Performancementioning
confidence: 99%
“…Maintaining a constant weight distribution is easier for athletes than for non-athletes. Therefore, athletes have a lower body sway 12–14 .…”
Section: Discussionmentioning
confidence: 99%
“…These specific neural adaptation mechanisms are due to strength training in the claimed muscles and are lead back to intra- and intermuscular coordination processes. Maintaining a constant weight distribution is thus easier for athletes than for non-athletes, because a smaller body sway can be registered 12–14 .…”
Section: Introductionmentioning
confidence: 99%